2010
DOI: 10.1128/jcm.00184-10
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of the Fungus Geosmithia argillacea in Sputum of People with Cystic Fibrosis

Abstract: We report the repeated isolation of the fungus Geosmithia argillacea from sputum samples of people with cystic fibrosis. Identification was based on morphology and DNA sequence analysis. Isolation of G. argillacea did not appear to be associated with clinical deterioration. The pathogenic potential of G. argillacea is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
47
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(51 citation statements)
references
References 7 publications
(5 reference statements)
3
47
1
Order By: Relevance
“…Since its first description in humans as Penicillium emersonii (2), then as Geosmithia argillacea (12,13), and finally as R. argillacea (1), the number of case reports involving the R. argillacea species complex is dramatically increasing in patients with CF or CGD. Accordingly, 24 out of the 27 patients included in the present study were diagnosed since 2005 and 15 of them since 2010.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since its first description in humans as Penicillium emersonii (2), then as Geosmithia argillacea (12,13), and finally as R. argillacea (1), the number of case reports involving the R. argillacea species complex is dramatically increasing in patients with CF or CGD. Accordingly, 24 out of the 27 patients included in the present study were diagnosed since 2005 and 15 of them since 2010.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic granulomatous disease (CGD) (9, 10, 11) and cystic fibrosis (CF) (12,13,14,15,16,17) are the major underlying clinical conditions. Rasamsonia infections may also occur in bone marrow transplant recipients (18, 19) but also may occur in the absence of any predisposing factors, as evidenced by the pulmonary and aortic graft infection reported by Doyon et al (20) in an immunocompetent individual.…”
mentioning
confidence: 99%
“…With the advent of molecular methods, it is now possible to resolve the phylogenetic and taxonomic relationships among these fungi. As summarized in Table 2 Geosmithia argillacea is a common thermotolerant environmental mold that has recently been reported as a cause of invasive fungal infections in patients with chronic granulomatous disease (25) and as a chronic respiratory tract colonizer in patients with cystic fibrosis (53). Following a molecular analysis that showed that Geosmithia is polyphyletic, Houbraken et al (26) created a new genus, Rasamsonia, to accommodate G. argillacea and a number of related species.…”
Section: Gattii) and Vgiii (C Bacillisporus)mentioning
confidence: 99%
“…In 2009, a fatal case of disseminated infection in a German shepherd dog was reported (5). Subsequently, eight cases of airway colonization in patients with cystic fibrosis, without evidence of clinical infection, were reported (4,10). Nine cases of pulmonary infections in patients with chronic granulomatous disease have been reported, two of which involved the chest wall and ribs and one of which disseminated to the brain (2,3).…”
Section: Case Reportmentioning
confidence: 99%